Greenland, Kejser Franz Joseph Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 3, 1931. Kaiser Franz Josef Fjord. In background on left: Attestupan on Fraenkels Halfo. Payer Spitze on the north side of Suess' Land is next to Attestupan but on south side of the fjord at the bend. Background at center: S.E. side of the fjord formed by mts. on Suess' Land. See Aerial Reel 18-19. Photo taken from S.S. Veslekari looking E.N.E.